The Use of Adverbials of Time in Bimanese Language: A Case Study in Bajo Village - Yeni Karlina; Furqanul Hakim; Saraswati Haylian Chiani (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2022)
This study aims to determine the category of using adverbs of time in Bimanese language and how the Bimanese use adverbs of time in the sentences. The samples of this study were eight participants, the native speakers of Bimanese language in Bajo Village. The data research were obtained by means of interviews, observation, audio recording, and taking note. The category of using adverb of time in Bimanese language consists of three categories. First was present category. The researchers found three categories used by Bimanese people, namely: simple present, present continuous, and present perfect. The second category was past tense. There were three categories used by the Bimanese people, namely: simple past, past continuous, and past perfect. The third category was future. In this category the researchers only found one category, namely future time.